Quercetin improves lacrimal gland function through its anti-oxidant actions: Evidence from animal studies, and a pilot study in healthy human volunteers - Inaba, Takaaki; Ohnishi-Kameyama, Mayumi; Liu, Ying; Tanaka, Yasuhisa; Kobori, Masuko; Tamaki, Shusaku; Ito, Tomotaka; Higa, Kazunari; Shimazaki, Jun; Tsubota, Kazuo (Frontiers in Nutrition, 2022)
Anti-oxidant properties of polyphenols have been gaining medical attention as a preventive factor against aging and/or lifestyle diseases. In this study, we examined the anti-oxidant activity of quercetin improved tear function through its effects on the lacrimal gland in mice and humans. Six week-old diabetic mice, a model for decreased tear production, were fed for 12 weeks ad libitum with an experimental diet containing 0.5% quercetin. As a result, the tear volume was significantly improved compared to the control, despite no changes in body weight, food intake, lacrimal gland morphology or biochemical serum parameters. Moreover, significantly higher SOD-1 and SOD-2 protein levels were detected in the lacrimal glands of quercetin-treated mice by western blot. In addition, quercetin treatment of mouse corneal cell lines exposed to oxidative stress resulted in dose-dependent inhibition of ROS production and enhanced cell survival. Finally, we examined quercetin pharmacokinetics, specifically its presence in serum and tears subsequent to onion consumption in healthy volunteers, and found that the distribution of quercetin and its metabolite shifted from serum to tear following onion intake. An improvement in tear film stability also resulted following the intake by these healthy volunteers of a new, quercetin-rich onion cultivar (”Quergold”) in powder form.